GERAKAN SIMBOLIK KULTURAL MASYARAKAT ADAT SENGWER MERESPON MARGINALISASI TERKAIT PENERAPAN PROGRAM NRMP DI CHERANGANY HILLS, KENYA - Suryawan, I Wayan Widyartha; Fasisaka, Idin; Parameswari, Anak Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRACT Natural Resource Management Project (NRMP) which is the domestic derivative of global conservation schemes Reducing Emissions from Deforestation and Forest Degradation (REDD), has led to the marginalization of Sengwer indigenous peoples in Cherangany Hills, Kenya. The Government of Kenya and the World Bank as the funders have violated the constitutional rights of Sengwer indigenous peoples. Responding to the marginalization, cultural symbolic movement emerged which put forward the concept of indigenous community-based conservation. Symbolic cultural movement is a form of new social movements. This movement seeks to fight for the rights of Sengwer  who are victims by application of the NRMP in Cherangany Hills, Kenya. This study aims to look at the symbolic cultural movement of indigenous peoples which is often regarded as a static society, a role responding to global conservation discourse. This study assessed using the concept of indigenous peoples and symbolic cultural movements; developmentalism; marginalization due to development; and theories of political ecology in developing countries. Keywords: symbolic cultural movement, marginalization, indigenous peoples, political ecology